2007
DOI: 10.1021/la062385q
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Adsorption Behavior of NAD+ at a Gold Electrode Surface

Abstract: The adsorption of an oxidized form of nicotinamide adenine dinucleotide, NAD+, on a polycrystalline gold electrode surface and the subsequent surface conformation of the molecule were investigated over a wide temperature and potential range, using electrochemical differential capacitance and PM-IRRAS techniques. The adsorption process was described by the Langmuir adsorption isotherm. The corresponding thermodynamic parameters were determined: the Gibbs energy, enthalpy, and entropy of adsorption. The large ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 54 publications
1
39
0
2
Order By: Relevance
“…According to the electrochemical double-layer theory [31], this decrease in the double-layer capacitance indicates that adsorption of reaction species occurs during the NAD + reduction reaction. Our electrochemical and PM-IRRAS adsorption measurements done at more positive potentials, where NAD + cannot be reduced (from −0.5 to 0.4 V versus SCE) [43], confirmed that NAD + is the species that adsorbs on the electrode surface in this positive potential region, and that this interaction is spontaneous, strong and irreversible (Gibbs energy of adsorption is −41 ± 4 kJ mol −1 , depending on the adsorption potential and temperature). However, since the measurements presented in Fig.…”
Section: Potential-dependant Eis Behaviorsupporting
confidence: 69%
See 2 more Smart Citations
“…According to the electrochemical double-layer theory [31], this decrease in the double-layer capacitance indicates that adsorption of reaction species occurs during the NAD + reduction reaction. Our electrochemical and PM-IRRAS adsorption measurements done at more positive potentials, where NAD + cannot be reduced (from −0.5 to 0.4 V versus SCE) [43], confirmed that NAD + is the species that adsorbs on the electrode surface in this positive potential region, and that this interaction is spontaneous, strong and irreversible (Gibbs energy of adsorption is −41 ± 4 kJ mol −1 , depending on the adsorption potential and temperature). However, since the measurements presented in Fig.…”
Section: Potential-dependant Eis Behaviorsupporting
confidence: 69%
“…However, at reported "optimum conditions", only 10% of active NADH was formed on Au-Hg [13], while a higher yield, 50%, was obtained on Pt [13] and Hg [6]. Our experiments on a Cu electrode [30] have yielded a trend very similar to the one in Fig. 1b, but the highest yield of enzymatically active NADH formed was 73% at −1.0 V, while at −1.2 V a significantly higher amount, 53%, was obtained when compared to the gold electrode (Fig.…”
Section: Enzymatic Assay-number Of Electrons Involved In Nad + Reductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the direct regeneration of NADH, the cofactor NAD + is reduced at the electrode surface. Omanovic and coworkers have investigated and improved the performance of direct electrochemical regeneration of NADH by depositing Ru, 16 Pt, 17 Ni, 17 Au 18,19 and Pt-Au 19 on electrode surfaces. While this method has been shown to be effective, the high overpotential required for the reduction of NAD + along with the formation of enzymatically inactive NAD 2 dimers remain the two significant disadvantages.…”
mentioning
confidence: 99%
“…5.13 (white and grey bars) yield a common "volcano-type" behaviour (i.e. a maximum), which is quite common in the area of electrocatalysts development [21,71]. ln conclusion, PANI30/Ni50-1.85V electrocatalyst shows the highest electrocatalytic activity in the HER, and will further be compared to the control (Ni plate), Ni-RVC, and…”
Section: Influence Of Ni Deposition Potentialmentioning
confidence: 99%